Collective bargaining about corporate social responsibility - Laszlo Goerke; Nora Paulus (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2024)
If a profit-maximising firm credibly commits to an employment-enhancing Corporate Social Responsibility (CSR) objective in negotiations with a trade union, the union can reduce its wage demands. Lower wages, ceteris paribus, raise profits, while the increase in employment enhances the payoff of a wage-setting trade union. Therefore, both the firm and the trade union can be better off in the presence of a collectively bargained CSR-objective than in its absence. Accordingly, establishing a CSR-objective can give rise to a Pareto-improvement and can mitigate the inefficiency resulting from collective wage negotiations.
Keywords: D60; J51; M14; 330; Collective Bargaining; Corporate Social Responsibility; Employment; ParetoImprovement; Trade Union; Wages